Interactive Multimedia Based on Android: A Learning Management System in Elementary School - Aka, Kukuh Andri (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to improve student learning outcomes through the development of an interactive multimedia application based on Android as an online learning management system for elementary school students that is valid, practical, and effective. The application development uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of expert validators, teachers, and fourth-grade students of the elementary school Laboratory University of Nusantara PGRI Kediri. The research instruments included a media and language expert validation questionnaire, teacher and student response questionnaires, and student learning outcome tests. The results showed that the developed multimedia application met the valid criteria with an average score of 85.57%. The practicality of the application is classified as very practical based on the positive responses of teachers of 85% and students of 82%. The application effectiveness test showed a significant increase in student learning outcomes with an N-gain score of 66%, included in the fairly effective category. Thus, this application is feasible and recommended as an alternative online learning medium at the elementary school level. Further research is recommended to expand the scope and variety of application content.